The mitochondrial gene order and CYTB gene evolution in insects - F. S. Sharko; A. V. Nedoluzhko; S. M. Rastorguev; S. V. Tsygankova; E. S. Boulygina; A. A. Polilov; E. B. Prokhortchouk; K. G. Skryabin (Вавиловский журнал генетики и селекции, 2017)
Over millions of years of evolution, the genomes of modern insects have accumulated a significant number of mutations, which often can lead up a blind alley when carrying out phylogenetic research. Genomic differences between some representatives belonging to the same family or group are often so great that they demand using nonconventional methods of the phylogenetic analysis. It is known that molecular evolution goes by the way of not only single nucleotide substitutions, but also by larger genomic reorganizations, such as insertion or deletion of large genome fragments, and even changing the order of genes. Mitochondrial DNA genes (mtDNA) are quite often used as markers for phylogenetic research into many organisms including arthropods, because mtDNA is multicopied, is inherited maternally, does not undergo recombination and accumulates mutations quickly enough (relative to the nuclear genome). To date, a large number of full nucleotide sequences of mitogenomes (thousands of organisms) has been deposited in public databases; however, their phylogenetic analysis has obstacles, especially for representatives of the insects (Insecta), whose evolution takes a considerable part of geological time. In this work we describe the application and a comparison of two ways of the phylogenetic analysis for different groups of insects. The first method uses the variability of the nucleotide sequence of mtDNA, and the second one analyses the order of genes in full mitochondrial genomes of insects that can be used as an additional marker in phylogenetic research into representatives of the order Hymenoptera.